The Troubling Epidemic of Wife-Battering in Ogbaru and Onitsha North Local Government Areas of Anambra State, Nigeria - Edith, AREH, Chinwe; Ajah, Benjamin Okorie; Ezeanya, Oguejiofo C.P.; Ugomma, EZE, Ann; Onwuchekwe, Stanley Ikenna; Onyejegbu, Chukwuemeka Dominic (International Journal of Criminology and Sociology, 2021)
Purpose: Debates and assumptions on the trend, motives/causes and implications of wife-battering in Nigeria are largely speculative. The purpose of this article is to explore in a raw form, the socio-economic determinants of wife-battering, on the sub-areas of family violence. Methods: Using qualitative and quantitative research methods, a sample of 364 respondents comprising 196 males and 168 females was drawn from Anambra State, Nigeria. Multi-stage and purposive sampling techniques were used to reach the respondents. Questionnaire and in-depth interviews were instruments for data collection. Results: Findings confirmed that wife-battering in Ogbaru and Onitsha-North Local Government Areas is most often caused by denial of sex and infidelity. Conclusion: The policy implications calls for the creation of local government welfare units to be holding periodic talk shows for married couples on the imperative of living happily.